The use of snow concepts in practical reindeer herding - Inger Marie Gaup Eira; Svein D. Mathiesen (Septentrio Academic Publishing, 2021)
Snow is important for reindeer herding in many ways, including maintaining thesupply of food, tracking, traveling, and the ability for the reindeer to graze. Snowhas a complex structure, which is constantly changing, and requires that reindeerherders know the strategies to adapt the herding to changing weather and snowconditions. This article deals with the question of how reindeer herders use snowconcepts in practical daily herding. In this research we have applied linguisticand interdisciplinary approaches. Furthermore, herding monitoring diaries havebeen used as a central tool, where herders from fivesiidas(reindeer herding communities)have monitored daily variations in grazing conditions. These herdingdiaries contribute detailed information on how Sami snow concepts are used indaily herding work. With this data, it is possible to gain insight into how reindeerherders use the snow concepts in connection with herding, and how herders assess the snow conditions in relation to the reindeer and the landscape, and howthey solve herding challenges in different situations in relation to these factors.Even though thesiidasbelong to the same reindeer herding region, the use ofsnow concepts shows variations in grazing conditions that are highly linked tospace, to differences in landscape and time, and how herders use the land. Theresearch shows that the use of the snow concepts is affected by the weather, wind,and temperature. Boazodollui lea muohta dehálaš máŋgga áššis, nugo riibadit biepmu, vuohttit, vánddarditja das movt boazu beassá guohtut. Muohttagis lea kompleaksa struktuvra, mii ovttat ládjerievdá ja gáibida ahte boazovázzit dovdet strategiijaid heivehit guođoheami rievdadeaddjidálke- ja muohtadiliide. Dát artihkal gieđahallá jearaldaga movt boazosápmelaččat geavahitmuohtadoahpagiid praktihkalaš boazobarggus. Dán dutkamis letne geavahan gielalaš jafágaidrasttideaddji lahkonanvugiid. Guovddáš reaidun lea adnon guođohanbeaivegirji, maidvihtta siidda geavahedje gozihit iežaset beaivválaš guohtundili. ...